Strategi Pembelajaran Aktif di Madrasah - Sus Rahma Yuni; Sahroina Rambe; Gusmaneli Gusmaneli (Pusat Riset dan Inovasi Nasional, 2024)
Active learning is a learning method that encourages student activity in the learning process. Active learning strategies are steps designed to involve students directly in the teaching and learning process so that they can understand and remember the material better.This research aims to identify active learning strategies that are effective in increasing student understanding. By reviewing literature and related research, we identified several active learning strategies that can be used in learning, such as group discussions, simulations, role plays, and problem-based projects. The research results show that these active learning strategies are effective in improving students' understanding because they allow students to be actively involved in the learning process. Apart from that, this strategy can also increase student motivation and promote collaboration between students.Thus, teachers and educators can consider using these active learning strategies in their lessons to improve student understanding. In the future, further research can be conducted to identify other active learning strategies that can increase learning effectiveness.